2007
DOI: 10.1093/molehr/gam026
|View full text |Cite
|
Sign up to set email alerts
|

Application of proteomic methods for identification of sperm immunogenic antigens

Abstract: Although the immunogenic properties of sperm have been explored for a few decades, none of the antigens studied so far appears to be an effective target, to inhibit the fertilization process or shown the full spectrum of sperm antigenic potential. Antisperm antibodies (ASA) collected from infertile individuals and prepubertal boys with cryptorchidism together with two-dimensional (2D) electrophoresis have been employed. Immunoreactive antigens were cored from silver stained 2D gels and analyzed by mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…Alpha-enolase was also found to be an isoantigen in women. This result confirms the results of Domagala et al [10], who studied cognate sperm antigens using the sera of ASA-positive infertile men and women. In our study, alpha-enolase was, however, firstly reported as a significant sperm antigen detected by the serum pool of infertile women.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Alpha-enolase was also found to be an isoantigen in women. This result confirms the results of Domagala et al [10], who studied cognate sperm antigens using the sera of ASA-positive infertile men and women. In our study, alpha-enolase was, however, firstly reported as a significant sperm antigen detected by the serum pool of infertile women.…”
Section: Discussionsupporting
confidence: 91%
“…To identify internal/external sperm antigens, protein extract must be prepared with a high degree of heterogeneity. Nonionic detergents [10] in general and Triton X-100 in our study have been reported as a suitable detergent [11] to solubilize proteins, and is compatible with our proteomic approach. The determination of sperm stress proteins, such as a group of HSPs, calreticulin and 78 kDa glucose-regulated protein, shows that they might be also involved in female sensitization.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Several approaches have been exploited for identification of epididymal proteins such as use of lectins (Srivastav 2000), sera from infertile patients (Primakoff et al 1990, Bohring & Krause 2003, Bhande & Naz 2007, mAbs (Hegde et al 1991), subtractive screening of cDNA library (Kirchhoff 1998), computational biology (Penttinen et al 2003), micro-array (Johnston et al 2005), neonatal tolerization (Ensrud & Hamilton 1991, Khole et al 2000, and proteomics (Syntin et al 1996, Naaby-Hansen et al 1997, Shetty et al 1999, Domagała et al 2007. Proteomics has also been applied to evaluate different aspects of normal sperm function , Ficarro et al 2003, Baker et al 2005).…”
Section: Introductionmentioning
confidence: 99%